Dialog Profetis: Misi Gereja Bagi Umat Transmigran di KeuskupanTanjung Selor, Kalimantan Utara - Siagian, Joan Nami Pangondian; Nono, Fredirikus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
The focus of this study is prophetic dialogue of the church’s mission for domestic migrants in the Diocese of Tanjung Selor, North Kalimantan. The socalled prophetic dialogue is very relevant to be applied in the Diocese. The local church is an example of the multi-cultural face of the Church. The Diocese of Tanjung Selor has greatly been influenced by the presence of migrants who come in from the various tribes and cultures throughout the country. The theological method used in this study is that of Stephen B. Bevans’ theological endeavors. Based also on the theology of Second Vatican Council, such as the Decree of Ad Gentes and referring to the thoughts of today’s theologians, the article promotes the prophetic dialogue to be taken into consideration within the Diocese. This research will specifically discuss how the prophetic dialogue is applied to migrant workers.